Effect of Buoyancy Force on the Flow Field in a Triangular Cavity (Global Journal of Science Frontier Research, 2014)
In this paper, the effect of buoyancy force in a triangular enclosure are studied numerically. The governing differential equations are solved by using finite element method (weighted-residual method). Here the left wall of the triangle is assumed to be adiabatic, the right and horizontal wall are kept at cold and heated respectively. Also all the wall are assumed to be no-slip condition. The effective governing dimensionless parameters for this problem are Rayleigh number, Prandtl number and Hartmann number.
Keywords: buoyancy force; finite element method; hartmann number; triangular cavity